Wireless insoles to measure ground reaction forces: step-bystep validity in hopping, walking, and running - Burns, G. T.; Zendler, J. D.; Zerrnicke, R. F. (ISBS Proceedings Archive (Michigan), 2017)
This investigation assessed the validity of force measurements from wireless shoe insoles against a force plate and an instrumented treadmill. Thirteen subjects performed hopping tasks on a force plate and walked and ran on an instrumented treadmill while wearing the insoles. Ground reaction forces were measured with the two systems and analyzed perstep and per-hop to assess the accuracy and validity of the insoles. Peak force, contact time, and impulse were calculated for each step, and peak force for each hop. Across all measures, the insoles demonstrated high agreement with the force plate and the treadmill. Intraclass correlation coefficients ranged from 0.81-0.96. The wireless insoles appear to be a valid tool for ground reaction force measurement, and current results support the use of these devices for biomechanical studies outside the laboratory and in the field.